Indeks Kepuasan Masyarakat (IKM) Pada Mal Pelayanan Publik Kota Banjarbaru Tahun 2022 - Rizky Subhan Rizky Subhan (Universitas Lambung Mangkurat, 2023)
In this study, the Banjarbaru City Public Service Mall will be the object of this study. The research aims to analyze the community satisfaction index (IKM). Provisions regarding the community satisfaction index (IKM), according to the Minister of Administrative Reform where there is a decree number 14 of 2017 concerning general guidelines for compiling the community satisfaction index for government agency service units. The approach used in this study is a quantitative method approach, with measurements using a Likert Scale. The sample used in this study was 150 respondents, with the sampling technique of probability sampling. Data analysis techniques in this study were analyzed beforehand by testing the validity and reliability tests then processing the data with a data tabulation system to draw conclusions about the community satisfaction index. The overall community satisfaction index for all indicators obtained an IKM value of 3.94 and an IKM conversion value of 78.8 which is in the category of service quality B and is in the good performance category. This shows that the services provided by public service mall officers are carried out properly. So that people are satisfied with the performance of the Banjarbaru city public service mall. Keywords: Public Service, Community Satisfaction, Community Satisfaction Index, Public Service Mall